2017
DOI: 10.1016/j.ajic.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-based surveillance of hospital-acquired respiratory virus infection in a tertiary care hospital

Abstract: Of 7,772 laboratory-confirmed cases of respiratory viral infection among hospitalized patients, 22.8% were categorized as having hospital-acquired infection. The overall incidence of hospital-acquired respiratory viral infection was 3.9 (95% confidence interval, 3.7-4.1) cases per 1,000 admitted patients. Rhinovirus was the most common virus (30.3%), followed by influenza virus (17.6%) and parainfluenza virus (15.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
(8 reference statements)
4
9
0
Order By: Relevance
“…Finally, respiratory viruses other than influenza comprised 80% of cases of VAHAP and one half of all cases of nosocomial pneumonia. This coincides with the findings of previous studies, in which the main viruses identified in patients with HAP were rhinovirus, respiratory syncytial virus, parainfluenza and coronavirus (21,23,(27)(28)(29). This highlights the relevance of infection control measures in preventing the spread of respiratory viruses from patients, caregivers and healthcare personnel, focusing not only on individuals with influenza-like illness, but also those with common colds or other respiratory symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, respiratory viruses other than influenza comprised 80% of cases of VAHAP and one half of all cases of nosocomial pneumonia. This coincides with the findings of previous studies, in which the main viruses identified in patients with HAP were rhinovirus, respiratory syncytial virus, parainfluenza and coronavirus (21,23,(27)(28)(29). This highlights the relevance of infection control measures in preventing the spread of respiratory viruses from patients, caregivers and healthcare personnel, focusing not only on individuals with influenza-like illness, but also those with common colds or other respiratory symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…In this work, it was observed that the incidence of hospital-acquired SARS-CoV-2 infection within a single large health system during a period of universal admission testing was relatively low. Other reports have found annualized hospital-associated respiratory viral infection rates to be ~4.9 (95%, 4.7–5.2) cases per 10 000 patient-days [ 9 ], consistent with the upper range of our estimate for SARS-CoV-2. As health systems and public health authorities communicate the need to avoid foregoing necessary clinical care, transparent enumeration of the risks of SARS-CoV-2 transmission within health care settings will be essential.…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted in the U.S., RSV infection comprised 8.3% of acute respiratory illnesses among the elderly; this proportion was 4% in a French study 13 , 14 . In Korean studies, laboratory-confirmed RSV infection accounted for 2.8% of all respiratory viral infections and 12.7% of hospitalizations on account of respiratory viral infection 15 , 16 . However, the percentage of RSV among all respiratory illnesses including bacterial infection in Korean adults had not been reported.…”
Section: Discussionmentioning
confidence: 99%